Quantifying the role of soil in local precipitation redistribution to vegetation growth - Xinrong Zhu; Hongyan Liu; Yunyun Li; Boyi Liang (Ecological Indicators, 2021)
Precipitation is the primary source of water available to vegetation. Although many studies have explored the spatially heterogeneous relationship between vegetation and precipitation, it remains unknown why different precipitation levels lead to comparable vegetation growth and the same precipitation level leads to different vegetation growth. Here we provided a simple, new parameterized calculation method to describe the precipitation-vegetation relation. The new method characterizes the ability of local precipitation to supply the water needed for vegetation growth. In the case of China, the method can explain vegetation growth better than the common indices that represent water supply, such as the SPEI, the PDSI, and soil moisture. We further explored what induces the differences in the capacity of soil to redistribute local precipitation for vegetation growth by examining the sensitivity of the residual value between actual vegetation growth and theoretical precipitation-determined vegetation growth to water storage-related soil properties. Our results indicate that soil texture and soil depth to bedrock rather than climatic factors predicted the above mentioned residual values, which implies that soil water storage capacity can increase or decrease the amount of local precipitation needed for vegetation growth. Soil physical properties that involve a high clay content and a thickness between 1 and 3 m are favorable for the stored precipitation fraction for vegetation growth. Neglecting this effect of soil water storage capacity may introduce inaccuracies when simulating the impact of future climate change on vegetation growth.